From meal to malfunction: exploring molecular pathways, biomarkers and interventions in postprandial cardiometabolic health - Reytor-González, Claudia; Cevallos-Fernández, Emilia; Jácome, Belén; Simancas-Racines, Daniel (Frontiers in Cardiovascular Medicine, 2025)
Cardiometabolic diseases—including type 2 diabetes, cardiovascular disease, and metabolic dysfunction–associated steatotic liver disease—are increasingly driven by near-continuous after-meal exposure to glucose and lipid surges that traditional fasting tests often miss. This review prioritizes human studies from 2020 to 2025 and uses earlier work only as foundational anchors; non-English reports were excluded and preclinical findings are cited solely for mechanistic context. Evidence converges on six processes that amplify risk within hours after eating: impaired insulin signaling, delayed clearance of dietary lipids, mitochondrial and oxidative stress, loss of endothelial nitric oxide, inflammasome-mediated inflammation, and microbiome–hormone interactions. Dynamic, after-meal markers and simple composites such as the triglyceride–glucose index outperform fasting measures for identifying risk and guiding care. Practical strategies to shorten the “damage window” include Mediterranean-style meals with low glycemic index swaps and unsaturated fats, earlier distribution of daily energy and early time-restricted eating, a small pre-meal protein portion, and brief post-meal walking. Fast-acting medicines—glucagon-like peptide 1 and glucose-dependent insulinotropic polypeptide receptor agonists, rapid-acting insulin analogues, sodium–glucose cotransporter 2 inhibitors taken before meals, and proprotein convertase subtilisin/kexin type 9 inhibitors—further blunt peaks, while continuous glucose monitoring with algorithmic feedback enables timing-aware, person-specific adjustments. A tiered workflow—screen, stratify, and personalize—reframes prevention and treatment around after-meal physiology, with particular relevance to settings where resources are limited.